Note on a 'Dag' or Pistol with Snaphaunce Lock and Pear-shaped Butt (Proceedings of the Society of Antiquaries of Scotland, 1915)
The lock is on the snaphaunce principle, that is, the nose of the sear projects through the lock plate and catches over a spur on the back of the doghead; the friction plate and pan-cover are independent pieces, the latter being slid off on the fall of the doghead by the thrust of an arm connected to the tumbler. There is no arrangement for half-cock. The lock plate is of brass incised with foliaceous scrolls and interlaced work, and bears the initials of the maker R.M. This is a fine specimen of this type of the earliest form of Scottish firearm. Dag-makers are to be found on the Hammermen Craft books during the sixteenth and seventeenth centuries, and their work is to be found not only in this country but abroad, the earliest dated example known being a pair in' the Museum at Dresden bearing the date 1598.